Analyzing the key factors and perspectives of stakeholders in pavement maintenance - Soni, Jaykumar; Gujar, Rajesh; Malek, MohammedShakil S. (Institute of Advanced Engineering and Science, 2025)
Road infrastructure is important for societal and economic development; therefore, it is crucial to maintain the durability and safety of the pavements. The present study investigates the domain of pavement maintenance by thoroughly analyzing the factors affecting the quality of pavement considering diverse groups of stakeholders. The study explored various flexible pavement defects (distress factors i.e., potholes, alligator cracks, longitudinal cracks, transverse cracks, hungry surfaces, streaking, shoving, rutting, and raveling). The opinions of stakeholders from various sectors such as public, private, and academia are collected through surveys, interviews, and detailed discussions. The collected data is analyzed using advanced statistical tools such as analysis of variance (ANOVA), post hoc test, criticality index, and Spearman rank correlation, which revealed patterns and correlations between stakeholder views. This study highlights diverse perspectives on pavement distress factors, providing valuable insights into the decision-making process. The findings of this research will help policymakers prioritize pavement maintenance based on the prevailing distresses, highlighting the importance of informed decision-making in pavement maintenance and management practices.